Triggering absorptive capacity: Why do the knowledge broker role of SME CEOs and organizational mechanisms matter? - Chauvet, Vincent (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2022)
Several articles call for more integrative models dealing with the identification of ACAP antecedents. Along with this idea, there is a growing need for further investigation to better approach the triggering of a knowledge absorption sequence. The objective is to highlight the impact of different organizational mechanisms as well as the knowledge broker role of SME CEOs in triggering and developing absorptive capacity. This study reveals on one hand the critical role of SME CEOs in triggering a knowledge absorption sequence. On the other hand, results underline that knowledge formalization and the codification of behaviors are effective mechanisms for the development of absorptive capacity.